The Role Of Woman To Protect Marine Plastic Waste In Sukabumi In Environmental Law Perspective (Study Case In Coastal Area In Pelabuhan Ratu) - Raden Eriska Ginalita Dwi Putri; Neneng Nurbaeti (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
nowadays marine pollution become a serious problem in the word, especially in Indonesia including in Sukabumi that known for itas beautifull beaches such as Pelabuhan Ratu, geopark ciletuh, ujung genteng, etc. marine marine scientists have found hamrful impact of marine pollution by plastic waste to the marine environment, ecosystem and human. there-quarter of all marine pollution in marine environment is plasctic. the situation become worse whe it come micro plastic woman have essential role to preseve the marine environment because woman have close relation to the environment